Perhitungan Harga Pokok Produksi Dengan Metode Full Costing: Penetapan Harga Jual Produk UKM Es Teh Aur - Afriani, Naira; Sumantri, Rahmanita; Hasdiyanti, Rizki; Ramadhani, Shefira (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the calculation of production costs using the full costing method: determining the selling price of (UKM) Es Teh Aur products. In an increasingly competitive beverage industry, accurate pricing is crucial to ensure profitability and business sustainability. The full costing method includes all production costs, both variable and fixed, providing a more comprehensive view of total expenses incurred. This research adopts a descriptive quantitative approach with purposive sampling conducted at UKM Es Teh Aur during the April 2025 period. Data were collected through direct observation and interviews. The analysis results indicate a significant difference between the company's cost of production calculation and the full costing method, with a discrepancy of IDR 200,000. The selling price calculated using the full costing method is also higher than the company's set price. These findings emphasize that the full costing method offers a more accurate basis for determining selling prices, helping to maximize profits and maintain product competitiveness